Mitigating the Effects of Transport Infrastructure Development on Ecosystems - Ghent, Carleigh (Consilience, 2018)
Transport infrastructure is one of the most important ways to help a country drive economic growth and alleviate poverty, but it can also have devastating effects on the surrounding ecosystems and wildlife. Habitat fragmentation and degradation, vehicle-wildlife collisions, population and genetic isolation, and loss of ecosystem services are just some of the effects roads can have on ecosystems and wildlife. This synthesis paper seeks to explore these effects and look at different ways to mitigate them to help restore ecosystems and the services they provide. Some ways to mitigate these effects include green infrastructure, corridors, and wildlife crossings. Green infrastructure provides more natural or semi-natural space for various ecosystem services, wildlife, and humans. Corridors connect the natural spaces created by green infrastructure and protected areas and allow movement of wildlife between these areas. Wildlife crossings can be overpasses or underpasses that lessen the barrier effects of transport infrastructure. Collaboration between multiple sectors, including governments, policy makers, transport infrastructure planners, ecologists, and geographers, is needed to create successful and both sustainable transportation networks and green infrastructure that support ecosystem services and functions.